Topological thinking in Bugis burial customs: Ethnomathematical insights from Mampu Cave - Jafaruddin; Tahmir, Suradi; Amda, Nayla Faiqah (Journal on Mathematics Education, 2025)
Mathematics has traditionally been perceived as abstract and disconnected from cultural practices; however, emerging ethnomathematical research suggests that sophisticated mathematical concepts are embedded within indigenous knowledge systems. This study employs an ethnographic approach to identify and analyze topological concepts within Bugis burial customs at Mampu Cave, Bone Regency, South Sulawesi, Indonesia. Through three months of fieldwork combining participant observation, semi-structured interviews, and mathematical analysis of burial structures, we documented the Sijello To Mampu petrification legend and examined spatial arrangements, carved patterns, and transformation narratives. The investigation revealed three levels of topological sophistication: homeomorphic transformations implicit in human-to-stone petrification narratives that preserve topological invariance; deliberate geometric symmetries and path-connected spatial arrangements in burial configurations; and a seven-crossing knot pattern in carved burial markers yielding a calculable Alexander Polynomial. These findings were systematized into a Realistic Mathematics Education (RME) framework progressing from concrete cultural experiences through abstraction to formal topological knowledge, integrating Bugis noble values (pangadereng) throughout. The study demonstrates that advanced topological thinking exists within traditional Bugis burial customs, challenging conventional boundaries between formal and informal mathematical knowledge while extending D'Ambrosio's ethnomathematical framework to encompass highly abstract mathematical domains. The developed educational framework integrates indigenous knowledge into advanced mathematics education, thereby contributing to curriculum decolonization and heritage preservation while enhancing engagement among students from similar cultural backgrounds.